Bio-stimulatory properties of a Lupinus albus L. seed suspension - Van der Watt, Elmarie (University of the Free State, 2005)
The sustainable increase in crop yields on available land, in light of an ever growing world population, remains an issue of importance for agronomists and plant physiologists alike. With this in mind, the underlying study was aimed at investigating the bio-stimulatory properties of a Lupinus albus L. seed suspension (SS) as well as its potential to be applied as a natural plant growth regulator in the horticultural and agricultural industries. Preliminary bio-tests, including the respiration rate of monoculture yeast cells, seed germination and seedling growth, strongly indicated that the rather crude seed suspension possessed the ability to manipulate these aspects when applied exogenously. SS significantly increased the respiration rate of monoculture yeast cells and, although it did not have a significant effect on seed germination, stimulated seedling growth in terms of coleoptile and root length in a number of crops at an optimal concentration of 5 mg L-1. Subsequently, the effect of SS on the yields of a variety of vegetable crops, flowers and cash crops was tested under field conditions at a concentration of 5 mg L-1. This concentration proved to be optimal for most vegetables, flowers, maize and wheat as either flower formation or yield of different crops were significantly enhanced. The most significant yield increases, after a foliar spray treatment with SS at an early growth stage, was observed in beetroot, lettuce and carrots under drip irrigation by increasing the yield with 9.3, 20.0 and 24.3 ton ha-1 respectively. This supplied the rationale for activity directed isolation and purification of the active bio-stimulatory compounds involved using standard chromatography techniques. By means of NMR spectroscopy and mass spectrometry the active compound was identified as a triglyceride, glycerol trilinoleate, and its structural formula elucidated. It was concluded from this study that the development of a natural product with growth regulating and yield enhancing properties should be considered strongly from a commercial perspective.

Die volhoubare verhoging in die oesopbrengs van landbougewasse op beskikbare grond is ‘n prioriteit vir beide agronome en plantfisioloë in die lig van ‘n groeiende wêreldbevolking. Met dit in gedagte is die onderhewige studie onderneem met die doel om die bio-stimulerende eienskappe van ‘n Lupinus albus L. saad suspensie (SS) te ondersoek asook die potensiaal om dit as ‘n natuurlike plantgroeireguleerder in die akkerbou- en tuinbou-industrieë toe te pas. Voorlopige bio-toetse, insluitende die respirasietempo van monokultuurgisselle, saadkieming en saailinggroei, het sterk daarop gedui dat die relatiewe ru saadsuspensie oor die potensiaal beskik om genoemde aspekte te manipuleer wanneer dit uitwendig aangewend word. SS het die respirasietempo van gisselle betekenisvol verhoog en, alhoewel dit nie veel van ‘n effek op saadkieming gehad het nie, het dit saailinggroei in terme van koleoptiel en wortellengte betekenisvol gestimuleer teen ‘n optimum konsentrasie van 5 mg L-1. Gevolglik is die invloed van SS op die oesopbrengs in ‘n verskeidenheid van groente-, blom- en kontantgewasse onder veldtoestande getoets teen 5 mg L-1. Hierdie konsentrasie was ook optimaal vir die meeste gewasse aangesien blomvorming in blomgewasse of oesopbrengs in ander gewasse betekensvol verhoog is. Statisties was die oesopbrengsverhoging mees betekenisvol in drupbesproeide beet, slaai en wortels na blaarbespuitings met SS op ‘n vroeë ontwikkelingsfase gemeet aan oesopbrengsverhogings van 9.3, 20.0 en 24.3 ton ha-1 respektiewelik. Laasgenoemde het die rasionaal verskaf om voort te gaan met die aktiwiteitsgerigte isolasie en suiwering van die aktiewe komponente betrokke deur van standaard chromatografietegnieke gebruik te maak. Deur middel van KMR spektroskopie en massaspektrometrie is die aktiewe komponent geïdentifiseer as ‘n trigliseried gliseroltrilinoleaat, en die struktuurformule ontsyfer. Uit hierdie studie is tot die gevolgtrekking gekom dat die ontwikkeling van ‘n natuurlike produk met groeiregulerende en oesopbrengs verhogende eienskappe vanuit ‘n kommersiële perspektief, sterk oorweeg moet word.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2005
Keywords: Lupinus albus L.; Seed suspension; Bio-stimulatory properties; Nuclear magnetic resonance (NMR) spectroscopy; Glycerol trilinoleate; Natural product; Plant regulators; Growth (Plants)